Healthcare professionals' perception of the ketogenic diet among patients with chronic obstructive pulmonary disease: a cross-sectional study - Alqarni, Saleha; Alsaeedi, Eatedal Eenizan; Siraj, Rayan A.; Aldabayan, Yousef Saad; Abdelhafez, Amal Ismael (Frontiers in Nutrition, 2025)
BackgroundChronic obstructive pulmonary disease (COPD) is a progressive respiratory disorder characterized by persistent inflammation and airflow limitation. The ketogenic diet (KD), recognized for its anti-inflammatory properties, has potential therapeutic benefits for COPD management. However, healthcare professionals' perceptions of KD's efficacy and applicability in COPD care remain underexplored, particularly in Saudi Arabia.MethodsA cross-sectional online survey was conducted between June and September 2024, targeting healthcare professionals involved in COPD management. The survey evaluated perceptions of KD's benefits, limitations, and current nutritional practices. Descriptive statistics and logistic regression analyses were performed using JASP to identify predictors of KD training uptake and the likelihood of discussing dietary interventions with COPD patients.ResultsA total of 1,068 healthcare professionals participated in the survey. Of these, 58% believed KD could improve quality of life in COPD patients, and 61% acknowledged its potential to reduce inflammation. Logistic regression identified familiarity with KD as significant predictor for receiving KD training (p < 0.001). Concerns regarding KD's adverse effects, such as constipation and dehydration, were noted by 76% of respondents. Only 14% reported recommending KD, citing insufficient evidence and lack of professional training as primary barriers. Additionally, 74% highlighted patient adherence challenges due to KD's restrictive nature and potential side effects.ConclusionKD shows promise as a complementary therapy for COPD by modulating inflammation and improving symptom management. Addressing barriers such as limited evidence and inadequate professional training is essential. Further research is required to establish the efficacy and safety of KD in COPD care.